Comparison in size and elemental composition of dust particles deposited to the surface and suspended in the air on the southwest Japan coast. (October 2015) - Fukushima, Satoshi; Zhang, Daizhou
Abstract: Input of dust to the ocean via the atmosphere is one of the key processes driving the development of marine ecosystems. It is usually estimated with dust concentration and deposition velocity on the assumption that particles settling to the marine surface are similar in composition to those in the air. In this study, we compared suspended and dry deposited dust particles which were collected at a seaside site on the southwestern Japan coast in two Asian dust episodes. Results show that particles mixed with sea salt and sulfate occupied 47–67% of the suspended dust particles while the percentage was 15–26% for the deposited particles. Sulfur and sodium contents in the deposited particles were apparently less than in the suspended particles. The mode size of the suspended ones, 2–3 μm, was a little smaller than that of the dry deposited ones, 3–5 μm. However, after being weighted by deposition velocity, it was similar to the latter one. These results support particle size as the key factor in determining the dry deposition and indicate the difference of suspended and deposited dust particles in the mixture with sea salt and sulfate in the marine atmosphere. Graphical abstract: Highlights: Suspended and deposited dust particles were collected at a coast site in Japan. The particles were compared according to their size and elemental compositions. More suspended particles mixed with sea salt and sulfate than deposited ones. Weighted mode of suspended particles was consistent to that of deposited ones. Size, not the mixture, was the key factor in determining the dust deposition.